Penerapan Pendidikan Karakter Berbasis Budaya Terhadap Siswa Sekolah Dasar Dalam Upaya Peningkatan Mutu Pendidikan Agama Hindu - Putu Wiwik Rismayanti (Jurnal Pendidikan Agama, 2021)
Globalization is caused by technological developments, economic progress and the sophistication of information facilities. The aforementioned conditions have had a positive impact as well as a negative impact on the Indonesian nation. The reality is that this is the biggest challenge for the world of education today. In fact culture cannot be separated from education, even culture is the basis or basis of education. This formula reaches far into the future, because it is said that education is not only based on an aspect of culture, namely the intellectual aspect, but also on culture as a whole. The culture on which this education is based must be national in nature. Thus the culture in question is real culture, namely the culture that lives in the Indonesian national society. This picture interrupts us to really pay attention to the importance of character building based on culture (Character building), with the development of technology in this era of digitalization, we are able to create students with culture-based characters and not abandon the development of the times, but use the development of this digitalization era to preserve, develop innovation with creativity that is owned to keep loving the heritage of our ancestors